Republic of the Marshall Islands : 2009 Article IV Consultation; Staff Report; a Public Information Notice; and a Statement by the Executive Director of the Republic of Marshall islands on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2010)
This 2009 Article IV Consultation highlights that the economy of the Marshall Islands is on a path to recovery. A gradual expansion with growth reaching 0.5 percent in 2010 is supported by further growth in the fish processing industry and additional foreign grant assistance. Rising prices could stoke inflation and stifle domestic demand. Executive Directors have encouraged the authorities to continue to strengthen the statistical base, especially the coverage and timeliness of fiscal and balance of payments data, in order to improve policy analysis and decision-making.